ANALISIS SISTEM KELISTRIKAN PADA PEMBANGKIT LISTRIK TENAGA SURYA ON-GRID KAPASITAS 25 KWP DI BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) PROVINSI BALI - Juniarta, I Kadek; Setiawan, I Nyoman; Dwi Giriantari, Ida Ayu (Jurnal SPEKTRUM, 2022)
In the 2020 fiscal year, the Ministry of Energy and Mineral Resources of the Republic of Indonesia provided PLTS On-Grid grants to the Province of Bali as many as 10 PLTS locations in Denpasar City. One of them is in the Regional Development Planning Agency (BAPPEDA) of Bali Province with an installed capacity of 25 kWp which is connected to the PLN network. BAPPEDA Bali is an example of the NRE Development Program and the Regional Medium- Term Development (RPJMD) that supports the PV mini-grid sector. This research was conducted to determine the performance of the PLTS electrical system and to simulate the results of PLTS production using Helioscope software so that it can compare the simulation results of 2 scenarios with real conditions to determine the level of effectiveness in saving electricity bills and the factors that influence the results of PLTS energy production. The results showed that the potential for electrical energy generated for a year from the simulation of Scenario 1 and Scenario 2 was 38.90MWh and 39.07MWh. It is known that the real energy production from July to December 2021 is 18,083 kWh with the simulation results of scenario 1 and scenario 2 from July to December 2021 which are 19,810 kWh and 20,015 kWh. The difference between real energy production and the simulation results in scenario 1 and scenario 2 is 1,727kWh with a percentage of 8.72%, and 1,931kWh with a percentage of 9.65%. The percentage of savings obtained for 6 months in 2021 compared to 6 months in 2020 is 56.42% with a saving value of Rp. 18,783,953.